Antimicrobial Activity Of Bael, Cinnamon And Neem Extracts Against Common Oral Microorganisms – An In-Vitro Comparative Study (Journal of Pharmaceutical Negative Results, 2022)
Aims: To assess the in- vitro antimicrobial activity of Bael, Cinnamon, and Neem extracts on Streptococcus mitis, Streptococcus mutans, Enterococcus faecalis, Campylobacter rectus , Porphyromonas gingivalis and Candida albicans and to compare it with the gold standard Chlorhexidine (0 .2 %) .Methods and Material: Leaves of Bael, Neem and Cinnamon barks were washed, shade dried and powdered individually. Cold maceration technique was used to prepare the ethanolic extracts of the test products. The standard strains of the selected test pathogens were procured and incubated in their respective selective media for upto 48 hours. The antimicrobial property of the test products at three different concentrations (0.1 %, 0.2 % and 0.3 %) was assessed using the Zone of inhibition by Agar Well diffusion method.Results: Bael leaf extract (0. 3%) had the highest zone of inhibition against Streptococcus mutans, Enterococcus faecalis, Campylobacter rectus and Porphyromonas gingivalis compared to 0. 3% Neem, 0.3 % cinnamon and 0. 2% chlorhexidine . With regard to Streptococcus mitis, 0 .2 % Chlorhexidine had the highest zone of inhibition compared to the herbal extracts. Among the tested products , only 0. 2% Chlorhexidine and 0.3 % Cinnamon extract had an antimicrobial activity against Candida albicans.Conclusions: Bael extract (0 .3 %) had the highest antimicrobial property against common oral microorganisms when compared to cinnamon extra ct (0. 3%), neem extract (0.3 %) and Chlorhexidine (0. 2%). However, Bael and neem did not exhibit any antifungal property